Analisis Geomorfologi dan Zona Potensial Akumulasi Air Sebagai Dasar Pemodelan Sistem Mine Dewatering pada Tambang Batugamping di Desa Topogaro, Kabupaten Morowali, Sulawesi Tengah - Chrisman Lanabu; T. Listyani Retno Astuti; Winarti Winarti; Ev. Budiadi (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Limestone mining activities in Topogaro Village require effective water management because carbonate geomorphology tends to produce complex flow pathways and increase surface and subsurface water accumulation. This study aims to identify water accumulation risk zones by integrating slope analysis, watershed delineation, Topographic Position Index, and ASTER spectral interpretation to support the design of mine dewatering systems. The methodology includes DEM sink filling, topographic parameter calculation, flow accumulation analysis, TPI classification, and carbonate mineral extraction using band ratios and principal component analysis. The results indicate that sub-watersheds W3 and W4 exhibit the highest flow accumulation and serve as the main contributors of runoff towards the central lowlands. The TPI categories valley and flat reinforce the identification of inundation-prone zones especially when aligned with dolomite-rich lithology and alteration zones characterized by high permeability. The discussion demonstrates that integrating geomorphological and spectral parameters effectively maps hydrological risks in tropical carbonate mining environments. The study concludes that low-slope areas with concentrated flow pathways are the primary priority for locating mine dewatering systems and designing runoff mitigation strategies. These findings provide an essential foundation for developing more accurate and adaptive dewatering designs in limestone mining operations.